V.M. Bekhterev`s Pedagogical Institute for Social Breeding and Research of the Normal and Defective Child (1921-1925): Theoretical and Applied Value - Dolgova E.A.; Hivinova D.A. (Психолого-педагогические исследования, 2018)
In article is covered the history of one of interesting educational institutions of the beginning of the 1920th – Vladimir Bekhterev`s Pedagogical institute for social breeding and research of the normal and defective child acting as a part of Psychoneurological academy in 1921-1925. Addressing unpublished documentation from funds of the Central state archive of St. Petersburg, the State archive of the Russian Federation, authors reconstruct history of creation and feature of functioning of Institute, investigate its scientific educational program and possibilities of its realization in practice, characterize structure and dynamics of training of students, place emphasis on establishment of interrelation of Institute with other institutions and laboratories of Psychoneurological academy, providing his functioning infrastructure. Authors draw a conclusion that the Vladimir Bekhterev`s Pedagogical institute for social breeding and research of the normal and defective child became useful experience of coordination of theoretical researches and applied developments in field of experimental pedagogics of the 1920th. Classical psychoneurological theories, on the one hand, and the ideas of the doctrine of V.M. Bekhterev - reflexology (individual and collective) - with another have been the basis for an institution. The educational program offered as a result differed from existing at that time and assumed attention to a labor element of education and a priority of a practical training over theoretical. The last answered the essential tasks set for scientific community and it was demanded in the early twenties: the project has got public financing and support. Though the idea of Institute was impractical, it reflects a bright, contradictory and interesting era of experimental science in the 1920th.